2022
DOI: 10.3389/fsufs.2022.881434
|View full text |Cite
|
Sign up to set email alerts
|

Usage of biological chitosan against the contamination of post-harvest treatment of strawberries by Aspergillus niger

Abstract: Developing bioactive food packaging, capable of extending the shelf life of fruits, has received increasing attention in recent years. The present study highlights the interest in post-harvest treatment for strawberries with chitosan as a preservation solution. Chitosan extraction was carried out from shrimp shells (Parapenaeus longirostris), composed of chitin, using citric acid during the demineralization step. Extracted chitosan was characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In the same report, an attack by A. alternata was revealed on the samples analyzed with a percentage of contamination ranging from 19.8 to 23.4% depending on the varieties studied. A study done by El-araby et al (2022) reported that the fungal strain A. niger was isolated from spoiled strawberries.…”
Section: Resultsmentioning
confidence: 99%
“…In the same report, an attack by A. alternata was revealed on the samples analyzed with a percentage of contamination ranging from 19.8 to 23.4% depending on the varieties studied. A study done by El-araby et al (2022) reported that the fungal strain A. niger was isolated from spoiled strawberries.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been obtained in previous studies. El-araby et al (2022) reported that the X-ray diffraction pattern of chitosan extracted from shrimp shells revealed two characteristic diffraction peaks at 2θ around 20° and 30°, which are typical fingerprints of crystalline chitosan character [ 26 ]. Another study reported that XRD studies of chitosan showed the maximum peak at 20.04° (113.92 counts/s), corresponding to chitosan crystalline nature [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) shows that chitosan produced from shrimp shells had a smooth and homogenous surface [ 25 ]. A study done by El-araby et al (2022) reported that the micrographs of shrimp shell chitosan showed a relatively smooth top surface and fibrous structures [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations